Lexicalização e neologismo: análise funcional em corpus digital - Souza, Adílio Junior de (2015)
This dissertation points out how the appearances of the neologisms in a language, by lexicalization, can contribute to enrichment and updating of the lexicon of the same language. Therefore, it looked for: (i) expose the main concepts about lexicon, neologism and lexicalization, based on the Usage-Based Linguistics (UBL), (ii) it presents 13 lexical items selected from the digital corpus and (iii) present the real relevance of the lexicalization for the formation of new words, for to understand how this affects/changes the multi-system. The corpus used was the one of the Project AC/DC: corpo Corpus Brasileiro, which has about one billion words employed in the most varied use contexts. For the fundamentation of the dissertation, some scholars were consulted, among them we highlight: Martelotta (2011), Gonçalves (2011), Contiero and Ferraz (2014), Correia and Almeida (2012), Carvalho (2009a), Biderman (1981), Câmara Jr. (2011), Pontes-Ribeiro (2007), Castilho (2003a; 2003b; 2008), Cunha (2011), Mendes and Seabra (2006), Ferraz (2006; 2007) and Fortunato (2008). The methodology consists in three stages: a) select of lexical elements samples in the corpus, b) extraction of this samples and compilations of them in tables and c) analyses of collected data. The results revealed that some of the 13 lexicalized words/neologisms, possibly, appeared to fulfill an existing space of linguistic signs in the multi-system, others acquired new meanings when used in new contexts of use and many others are in process of disappearance. The frequency of use was determining in the change of meaning.